7. Penerapan Model Pembelajaran Kontekstual Melalui Pendekatan Tematik Untuk Meningkatkan Hasil Belajar Siswa Di Sekolah Dasar - Alfiah, Siti; ., Supriyono (JURNAL WAHANA PENDIDIKAN DASAR, 2017)
Learning student days now in demand to be more active in learning kegeiatan. Not only that, but students are also in demand untu connect each subject to one another and can menerpkan in everyday life. The problems faced in learning activities in class V SDN Ketintang II Surabaya is the low interest of students in learning terajdi because teachers still use the lecture method is conventional. Submission of materials with the lecture method makes students often feel tired and boring, lack of teachers using an interesting method has not been implemented as well as connect with the subject matter of the other subject matter is still weak and lacking. Therefore the solutions offered in this study is penerpan contextual learning model through a thematic approach to improve student learning outcomes. The purpose of this research is to describe the activities of teachers in improving student learning outcomes siswa.Mendeskripsikan submarine activity following study and to describe student learning outcomes after application of contextual learning model through a thematic approach. Model of research is a class act consisting of two cycles. The subjects were students of class V SDN Ketintang II Surabaya with details of the male 16 and female 14. Grand Total students there are 30. Data were obtained from observation and tests. Data observation activities of teachers and students in the analysis as a percentage. Data from tests based on the percentage of students in the analysis of classical learning completeness. The results showed that the percentage of teachers' activities increased by 24.6%. Ie from 66.7% to 90.3%. Activities of students increased by 25.1% from 67.8% to 92.9%. While the learning outcomes of students has increased by 17.2% from 68.5% to 85%. Based on these results, mak recommended for elementary school teachers to try to implement contextual learning model approach teamatik especially the theme of harmony in society.